Increased platelet aggregation in hepatic tissue of metabolic-associated fatty liver disease—an observational study - Rongshan Fan; Yandong Li; Zeng Du (Frontiers in Medicine)
ObjectiveThe study aimed to observe the quantity of platelet aggregation in the hepatic tissue of patients with metabolic-associated fatty liver disease (MAFLD) and its relationship with hepatic inflammation, fibrosis, and fatty degeneration.MethodsClinical data of 55 patients with MAFLD and 25 patients without MAFLD, admitted to the Shenzhen Hospital of Integrated Traditional Chinese and Western Medicine from December 2020 to May 2022, were retrospectively analyzed. Liver tissue obtained by liver biopsy underwent routine pathological examination. Immunohistochemical staining with CD63 antibody was performed to label platelets in the liver tissue. Clinical, liver pathology, and immunohistochemical staining data of the study subjects were statistically analyzed using unpaired t-test.ResultsThe quantity of platelet aggregation in the hepatic tissue was higher in MAFLD patients than in non-MAFLD patients and was related to the degree of hepatic inflammation but not to the degree of hepatic fibrosis or fatty degeneration.ConclusionThe quantity of platelet aggregation in hepatic tissue was increased in patients with MAFLD and was related to the degree of hepatic inflammation,